1986
DOI: 10.1111/j.1440-1827.1986.tb02836.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Features of Small Hepatocellular Carcinoma

Abstract: Twenty‐one nodules of small hepatocellular carcinoma (HOC) were examined. Hlstologically, the nodules often presented formation of plump trabeculae, marked nuclear atypism, or aggressive growth comprising capsular invasion, vascular invasion, and replacement of adjacent pseudolobules. Aside from these characteristic findings of HCC, it was important to reveal the following features for the diagnosis of well differentiated type of small HCC:(1) variable thickening or distortion of trabecular structure in associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…There is increased basophilic or eosinophilic cytoplasmic staining, which may be of diagnostic use. 21 For unknown reasons, tumor cells have a remarkable tendency to undergo fatty changes or clear cells alterations, especially in small nodules. Similar findings were also observed by Kojiro et al 22 In this study, BHC-treated liver showed small to large hepatocytes with enlarged nucleus and bigger nucleoli.…”
Section: Discussionmentioning
confidence: 99%
“…There is increased basophilic or eosinophilic cytoplasmic staining, which may be of diagnostic use. 21 For unknown reasons, tumor cells have a remarkable tendency to undergo fatty changes or clear cells alterations, especially in small nodules. Similar findings were also observed by Kojiro et al 22 In this study, BHC-treated liver showed small to large hepatocytes with enlarged nucleus and bigger nucleoli.…”
Section: Discussionmentioning
confidence: 99%
“…However, some patients who could not obtain a treated margin ≥5 mm showed definite local recurrence. This may have been due to incomplete necrosis of the marginal tumor area including microscopic metastasis adjacent to the primary tumor (10)(11)(12). Therefore, the treated margin of ≥5 mm should be obtained to eliminate tumor cells at the periphery and reduce the incidence of local recurrence (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Stromal invasion, formerly called interstitial invasion [13,14], is defined as invasive growth of tumor tissue into fibrous septa, portal tracts, and/or blood vessels [13][14][15][16][17]. It is histologically classified into 3 types: crossing, longitudinal, and irregular ( Fig.…”
Section: Histological Diagnosis Of Early Hccs Of Resected or Autopsiementioning
confidence: 99%